L‐type Voltage‐Gated calcium channels partly mediate Mechanotransduction in the intervertebral disc. Issue 4 (23rd June 2022) - Poillot, Philip; Snuggs, Joseph W.; Le Maitre, Christine L.; Huyghe, Jacques M.
Abstract: Background: Intervertebral disc (IVD) degeneration continues to be a major global health challenge, with strong links to lower back pain, while the pathogenesis of this disease is poorly understood. In cartilage, much more is known about mechanotransduction pathways involving the strain‐generated potential (SGP) and function of voltage‐gated ion channels (VGICs) in health and disease. This evidence implicates a similar important role for VGICs in IVD matrix turnover. However, the field of VGICs, and to a lesser extent the SGP, remains unexplored in the IVD. Methods: A two‐step process was utilized to investigate the role of VGICs in the IVD. First, immunohistochemical staining was used to identify and localize several different VGICs in bovine and human IVDs. Second, a pilot study was conducted on the function of L‐type voltage gated calcium channels (VGCCs) by inhibiting these channels with nifedipine (Nf) and measuring calcium influx in monolayer or gene expression from 3D cell‐embedded alginate constructs subject to dynamic compression. Results: Several VGICs were identified at the protein level, one of which, Cav2.2, appears to be upregulated with the onset of human IVD degeneration. Inhibiting L‐type VGCCs with Nf supplementation led to an altered cell calcium influx in response to osmotic loading as well as downregulation of col 1a, aggrecan and ADAMTS‐4 during dynamic compression. Conclusions: This study demonstrates the presence of several VGICs in the IVD, with evidence supporting a role for L‐type VGCCs in mechanotransduction. These findings highlight the importance of future detailed studies in this area to fully elucidate IVD mechanotransduction pathways and better inform treatment strategies for IVD degeneration. Abstract : This study investigated the expression and function of voltage‐gated ion channels in the intervertebral disc. One channel, Cav2.2, was found to be upregulated in degeneration, while L‐type voltage gated calcium channels were found to be involved in mediating calcium signaling and the response of disc cells to dynamic compression.